The diné educational philosophy (DEP) and its incorporation into the Associate of Science Degree Program in public health at diné college. - Garrison ER (Journal of Interprofessional Care)
Diné College was established by an Act of the US Congress in 1968 as the first Native American tribally-controlled college. It is chartered by the Navajo Nation and operates eight campuses to serve a reservation community spread over 25,000 square miles. In 2004, Diné College became the first tribal college to establish a degree program in Public Health, and, in accordance with the college's mission, considerable efforts have been made to incorporate Navajo language and cultural materials into the teaching curriculum of this degree program. Materials are presented here that have been developed not only by Diné College but also by the Department of Diné Education (of the Navajo tribal government) and by the Northern Navajo Medical Center (Indian Health Service). These materials describe some of the core philosophical concepts, both in Navajo and in English, some of the complex symbolism associated with these core concepts, and some of the applications to daily living that derive from these core concepts. The purpose for the use of these materials in the curriculum is to ensure that students, who are almost all Navajo, will be prepared for providing Public Health educational and intervention services that are well suited to the cultural environment of the Navajo People.